Oxygen evolution reaction activity and underlying mechanism of perovskite electrocatalysts at different pH. Issue 1 (26th November 2020) - Kim, Bae-Jung; Fabbri, Emiliana; Borlaf, Mario; Abbott, Daniel F.; Castelli, Ivano E.; Nachtegaal, Maarten; Graule, Thomas; Schmidt, Thomas J.
Abstract : The members of the perovskite oxide family have been vastly explored for their potential as active electrocatalysts for an efficient anodic reaction ( i.e. the oxygen evolution reaction, OER) of the water splitting process. Abstract : The members of the perovskite oxide family have been vastly explored for their potential as active electrocatalysts for an efficient anodic reaction ( i.e. the oxygen evolution reaction, OER) of the water splitting process. Therefore, restless effort has been invested in the development of perovskite oxides as efficient OER catalysts, while the OER mechanism is still in veil. The rational development of perovskite catalysts for practical water electrolysis is left on hold until the full comprehension of the underlying mechanism is established under real operation conditions. Up to date, primarily two different OER mechanisms – conventional and lattice oxygen evolution – have been conjectured where the former follows a reversible route while the latter leads to irreversible changes. In this present study, we present evidence which suggests that perovskite catalysts follow both mechanisms concomitantly while one is preferentially selected based on their thermodynamic and kinetic natures dependent on pH.